Navigating the Unconscious: The Symbolic Significance of Travel in Heart of Darkness - Muhammad Yousaf Khan; Nasir Jamal Khattak (University of Chitral Journal of Linguistics and Literature, 2024)
Travel is an intrinsic aspect of human existence. From the first explorations of new territories to modern-day secular travels, the act of moving across spaces shapes individuals and societies. This paper looks into the theme of travel in Joseph Conrad's Heart of Darkness from the point of view of Jungian analytical psychology.  It focuses on the impact of travel on the protagonist, Marlow.  Drawing on Jungian concepts such as the unconscious, archetypes, active imagination, and synchronicity, we study the symbolic layers of Marlow's journey.  We also touch on the historical evolution of travel, modern perspectives on secular travels, and the spiritual dimension of inner journeys.  Marlow's expedition through the Congo River highlights the intricate interplay between the inner and outer realities emphasizing the broader human quest for self-discovery and growth.